USE OF NATURAL RESOURCES IN COMBINATION WITH CHEMICAL TREATMENTS FOR INFLUENZA - Islamova Intizor; Bahriddinova Zulfizar (Scholar Express Journals, 2023)
This article provides comprehensive information on the use of chemical methods in the treatment of influenza. The virus is easily transmitted through air droplets, and that is why it spreads quickly in schools, kindergartens, offices and other crowded places. Most often, this disease is transmitted by a patient coughing or sneezing, but the virus can also be transmitted by shaking hands.
Keywords: Vaccine; hygiene rules; immunobiological methods; intoxication